2021
DOI: 10.1016/j.jbc.2021.101264
|View full text |Cite
|
Sign up to set email alerts
|

Hop2 interacts with the transcription factor CEBPα and suppresses adipocyte differentiation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Our result showed these morphological changes on the microscopy image as shown in Figure 3 A. During 3T3-L1 adipogenesis, C/EBP-α and PPAR-γ are activated by insulin with FBS [ 25 ]. We investigated the changes in the expression level of transcription factors such as PPAR-γ according to the application of MCS during adipogenesis.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Our result showed these morphological changes on the microscopy image as shown in Figure 3 A. During 3T3-L1 adipogenesis, C/EBP-α and PPAR-γ are activated by insulin with FBS [ 25 ]. We investigated the changes in the expression level of transcription factors such as PPAR-γ according to the application of MCS during adipogenesis.…”
Section: Resultsmentioning
confidence: 71%
“…We also confirmed that MCS leads to a decrease in the expressions of C/EBP-α and PPAR-γ, which are known as transcription factors in the adipogenesis. In other studies, a reduction in transcription factors has been mentioned as an efficient strategy for inhibiting lipid accumulation [ 25 , 43 ]. It supported the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The protein product consists of 217 amino acids in its monomer form, encoding a nuclear, tissue-specific protein with multiple functions, including a role in meiotic recombination and acting as a coactivator of ligand-dependent transcription mediated by nuclear hormone receptors, which is conserved in evolution (19,20). Previous studies demonstrated that, in PSMC3IP-knockout mice, the ovarian volume was reduced and germ cells were missing (21,22). PSMC3IP is a DNA-binding protein dimer, characterized by the presence of three domains including a leucine zipper domain, a DNA-binding domain and a RAD51/DMC1 interaction domain (13).…”
Section: Discussionmentioning
confidence: 99%
“…A BeyoRT™ II cDNA kit (D7170M; Beyotime) was used to synthesize cDNA as indicated by the manufacturer. PCR was measured using QuantStudio™ 5 (Thermo Fisher Scientific) with TB Green® Premix Ex Taq™ II (Tli RNaseH Plus) (RR820Q; TaKaRa) under the condition of 95°C/30 s, 40 cycles of 95°C/5 s and 60°C/30 s. Primers for C4b (forward: 5′‐ACCCCCAGTACTTGCTGGAC‐3′; reverse: 5′‐ACCCTGTAGAGCAGAGCCTCTAA‐3′), 17 Cebpa (forward: 5′‐AGGTGCTGGAGTTGACCAGT‐3′; reverse: 5′‐CAGCCTAGAGATCCAGCGAC‐3′), 18 Lyz2 (forward: 5′‐TGCCAGAACTCTGAAAAGGAATGG‐3′; reverse: 5′‐CAGTGCTTTGGTCTCCACGGTT‐3′), 19 Spp1 (forward: 5′‐AGCAAGAAACTCTTCCAAGCAA‐3′; reverse: 5′‐GTGAGATTCGTCAGATTCATCCG‐3′) 20 and Gapdh (forward: 5′‐AGAACATCATCCCTGCATCCA‐3′; reverse: 5′‐CCGTTCAGCTCTGGGATGAC‐3′) 19 were obtained from references. PCR results were obtained with 2Ct ${2}^{-\unicode{x02206}\unicode{x02206}{C}_{{\rm{t}}}}$ with the internal reference of Gapdh .…”
Section: Methodsmentioning
confidence: 99%